PERLINDUNGAN TERITORIAL INDONESIA DARI ILLEGAL FISHING DI TINJAU DARI HUKUM LAUT INTERNASIONAL - Sayfudin Achmad (Jurnal Pacta Sunt Servanda, 2022)
Fishermen catching fish violating the law have been around for a long time in Indonesian waters, even though various efforts have been made to prevent it or to prevent theft of fish by foreign fishermen. However, this criminal behavior is a matter that is very problematic for Indonesia, because this is a cross-border problem between countries, therefore the handling of this problem must be carried out cross-line, especially through mutual cooperation. Although there has been a mutual cooperation between Indonesia and several neighboring countries as well as the participation of the province in obtaining territorial waters.